Avaliação e intervenção na qualidade de vida dos pacientes com espectro da esquizofrenia - Silva, Artur Gevázio Lira da (2023)
The spectrum disorders of schizophrenia compose a distinct and quite characteristic group of psychopathologies, which have as central criteria the loss of contact with reality and the presence of functional impairments in the affective, cognitive, and behavioral spheres, also occurring damage in family and social relationships. These disorders are classified as chronic non-communicable diseases, being associated with functional disabilities and disabilities, significantly affecting various aspects of daily life, such as social relationships, family ties and activities related to income guarantee. Thus, any type of intervention that works with some of these aspects should seek to promote the quality of life and autonomy of the patient, since in chronic conditions, the promotion of quality of life becomes even more important, since the treatment is not curative, as in the case of severe and persistent mental disorders. Therefore, this conclusive technical report presents the process of elaboration of the technical products derived from this research. Namely, an informative e-book with information regarding the evaluation and intervention in the quality of life of patients with schizophrenia spectrum disorders, aimed at higher education professionals working in the Psychosocial Care Network and a booklet for caregivers of people with schizophrenia, as well as the users themselves. In addition, the research had generated two articles: one related to the current state of the literature on interventions aimed at increasing the quality of life of people with schizophrenia and another on the existing and validated psychometric instruments in the country for the evaluation of the quality of life of schizophrenics. To obtain the technical upholstery of the booklets, we resorted to a systematic literature review of publications that discussed aspects related to interventions with schizophrenic patients focused on improving quality of life, in addition to listing the instruments available for the evaluation of this construct. Subsequently, semi-structured interviews were conducted with the higher education professionals of the Regional Psychosocial Care Center of Tamboril, to collect information about their professional practice with the schizophrenic public. The speeches were transcribed and analyzed through Bardin's Content Analysis, in which the thematic categories that guided the construction of the booklet were obtained. The elaboration of the research allowed us to verify that the national literature on quality of life and schizophrenia, whether in the interventional scope, or in the psychometric instruments, is still quite scarce. Thus, the productions obtained, in addition to serving as scientific dissemination material for the public, with ways to clarify misconceptions about the spectrum, also brought contributions to this research gap still little explored in the country.